A STUDY ON THE TEACHER’S FEEDBACK IN THE CLASSROOM IN RELATION TO STUDENTS’ MOTIVATION AND ACHIEVEMENT IN LEARNING ENGLISH LANGUAGE FOR VII GRADE AT SMP NEGERI 1 BANJAR - ., Ni Wayan Wita Astiti S.; ., Drs.Gede Batan,MA; ., Putu Eka Dambayana S., S.Pd. (Universitas Pendidikan Ganesha, 2017)
Penelitian ini bermaksud untuk meneliti tingkatan umpan balik yang digunakan oleh guru di dalam kelas dalam mengajar bahasa Inggris dan meneliti hubungan antara umpan balik yang diberikan oleh guru dengan motivasi dan prestasi siswa. Penelitian ini menggunakan studi kasus deskriptif dan melibatkan seorang guru bahasa Inggris yang mengajar tujuh puluh empat siswa dari dua kelas. Pengumpulan data dilakukan dengan melakukan observasi, wawancara, dokumentasi, dan kuisioner. Berdasarkan temuan, guru menggunakan empat tingkatan umpan balik sesuai dengan teori dari Hattie&Timperley (2007); task level, process level, self-regulation level, dan self-level. Task level digunakan 10.76% di VII E dan 6.13% di VII F, process level digunakan 78.49% di VII E dan 65.31% di VII F, self-regulation level digunakan 7.69% di VII E dan 7.14% di VII F, dan self-level digunakan 3.06% di VII E dan 21.42% di VII F. Umpan balik dari guru berhubungan dengan motivasi dan prestasi siswa. Hal ini terbukti dari persentase motivasi dan prestasi siswa. 51.35% siswa memiliki motivasi yang tinggi, 48.65% siswa memiliki motivasi sedang, 63.5% siswa memiliki prestasi yang tinggi dan 36.5% siswa memiliki prestasi yang sedang. Kata Kunci : umpan balik, empat tingkatan umpan balik, motivasi, prestasi This study intends to investigate the level of feedback used by the teacher in the classroom in teaching English language and the relationship between the teacher?s feedback and students? motivation and their achievement. It utilized a descriptive case study and involved an English teacher who thought seventy-four students from two classes. The data were collected from an observation, an interview, a documentation, and a questionnaire. The findings showed that the teacher provided four levels of feedback as proposed by Hattie & Timperley (2007); task level, process level, self-regulation level, and self-level. Task level was used 10.76% in VII E and 6.13% in VII F, process level was used 78.49% in VII E and 65.31% in VII F, self-regulation level was used 7.69% in VII E and 7.14% in VII F, and self-level was used 3.06% in VII E and 21.42% in VII F. The teacher?s feedback had relationship with the students? motivation and achievement. It showed from the percentage of students? motivation and achievement. There were 51.35% students who had high motivation, 48.65% students who had moderate motivation, there were 63.5% students who had high achievement and 36.5% students who had moderate achievement.keyword : feedback, four levels of feedback, motivation, achievement